2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333571
|View full text |Cite
|
Sign up to set email alerts
|

Computerized optimization of biventricular pacing using body surface potential map

Abstract: An improvement of biventricular pacing (BVP) could be possible by detecting the patient specific optimal pacemaker parameters. Body surface potential map (BSPM) is used to obtain the electrophysiology and pathology of an individual patient non-invasively. The clinical measurements of BSPM are used to parameterize the computer model of the heart to represent the individual pathology. The computer model of the heart is used to simulate the dyssynchrony of the ventricles and myocardial infarction (MI). Cardiac el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…However, we speculate that in patients with LBBB, the conduction wavefront from the LV lead would be unable to traverse the interventricular septum because of LBBB; therefore, travel in an epicardial manner would dominate and, physically, the apex and RVOT would meet the excitation wave sooner than the mid‐septum. Miri et al 17 demonstrated this in a computer generated 3D model of the human heart adapted for investigation of optimal site for biventricular pacing. They used MRI and detailed ECG data from 10 patients and modeled differing electrode positions to obtain optimum synchrony.…”
Section: Discussionmentioning
confidence: 96%
“…However, we speculate that in patients with LBBB, the conduction wavefront from the LV lead would be unable to traverse the interventricular septum because of LBBB; therefore, travel in an epicardial manner would dominate and, physically, the apex and RVOT would meet the excitation wave sooner than the mid‐septum. Miri et al 17 demonstrated this in a computer generated 3D model of the human heart adapted for investigation of optimal site for biventricular pacing. They used MRI and detailed ECG data from 10 patients and modeled differing electrode positions to obtain optimum synchrony.…”
Section: Discussionmentioning
confidence: 96%